Bibliometric Analysis of The Term ‘Cooperative Learning Chemistry’ - Hidayah, Rusly; Dasna, I Wayan; Budiasih, Endang (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
Bibliometric analysis related to cooperative learning methods is a new theme and has never been studied. The research pattern related to cooperative learning methods is still uncharted and it is not known how effective it is when analyzed from several previous studies. Cooperative learning chemistry concepts provide suitable solutions for improving activity of students and chemistry learning outcomes. This study aims to demonstrate an all-compassing bibliometric analysis in the terms and concepts of ‘cooperative learning’. The articles evaluated were identified through Google Scholar database as well as the perish or publish software. Furthermore, scimagojr.com (Q1, Q2, Q3, and Q4) was adopted during scanning, and a total of 19 articles were analyzed from 7 reliable journals. This research using literature review method. The type of research used a bibliometric review in five measures method pioneered. These five steps describe the keyword of the search as cooperative learning chemistry, initial search results, improvement of these results, collection of initial data statistics and data analysis, as explained below. The results showed the practice of cooperative learning in chemistry is being widely accepted. However, there is a need for further research and Collaborations on inter-regional studies involving Asian scholars and developed nations in particular regions. The results showed that more than 75% of cooperative learning has a significant effect on learning outcomes. The learning model is an external factor that affects learning outcomes.